Penerapan Sistem Pemanenan Air Hujan Sebagai Upaya Antisipasi Bencana Kekeringan Di Dusun Sepi, Sekotong - Muhammad Khalis Ilmi; Muhammad Islamy Rusyda; Agustini Ernawati; Titik Wahyungingsih; Ari Ramadhan Hidayat; Anwar Efendy; Intan Novianti; Feri Irawan; Chairil Anhar (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
The threat of drought that occurs every year will have an impact on hampering the activities of residents Dusun Sepi, Buwun Mas Village, Sekotong District. Therefore, it is necessary to make efforts to overcome the threat of a clean water crisis due to drought by conserving water or looking for alternative water sources. The application of a rainwater harvesting system (PAH) can be a solution to this problem. The purpose of this community service activity is to provide socialization and applications regarding efforts to anticipate drought disasters. The method used is a knowledge approach by providing socialization and application of the PAH system in one of the buildings at the Zainul Hafidz Islamic Boarding School At-Taufiq, Dusun Sepi, Buwun Mas Village, Sekotong District. The socialization activity took place on June 4, 2022 and went smoothly and orderly. During the implementation of the service activities, partners, in this case the residents of the Zainul Hafidz At-Taufiq Islamic Boarding School and the residents of the quiet hamlet, were very enthusiastic in participating in the socialization and application of rainwater harvesting (PAH) or roof-based rain water harvesting on a household scale with 54 participants. who came from the residents of the Islamic boarding school and residents around Dusun Sepi. From the estimated demand for clean water for Islamic boarding schools, with the PAH system as an alternative water source, the fulfillment of clean water needs for Islamic boarding schools can be helped by 3%.